Trace element features of Palaeozoic detrital units of the Ossa-Morena Zone (Portugal): geodynamic constraints - ROSEIRO, José (2020)
Chemical features regarding the different detrital lithostratigraphic Palaeozoic (Cambrian – Devonian) units from the Portuguese sector of the Ossa-Morena Zone regist geochemical aspects typical of their depositional environment, which allow inferences on the geodynamic evolution of the Iberian Authoctonous Terrain during the Variscan Cycle. Trace elements relationships (essentialy Nb/Ta, Zr/Hf, Th/U, La/Th-Sc and REE chondrite-normalized patterns) of the detrital succession reveal that the different formations derive mostly from an acid continental source, though with features that suggest mixed sedimentary components. Cambrian, Ordovician and Silurian representative samples show significative influences typical of passive margin sediments, while Devonian samples appear to have an oceanic arc contribution, with an increase in basic components, which may indicate a transition on the tectonic environment, during their deposition. Ante-Devonian Variscan formations are therefore interpreted as representing debris deposition, derived from the progressive dismantling of a continental basement (Cadomian arc and Gondwana terranes), in sedimentary basins formed during the lower Cambrian crustal thinning episode. Contrastingly, Devonian units correspond to etasedimentary rocks derived from a dismembered (basic-intermediate) volcanic arc, revealing an active margin in the SW Ossa-Morena Zone during this period.